2010
DOI: 10.1093/cercor/bhq109
|View full text |Cite
|
Sign up to set email alerts
|

Painful Heat Reveals Hyperexcitability of the Temporal Pole in Interictal and Ictal Migraine States

Abstract: During migraine attacks, alterations in sensation accompanying headache may manifest as allodynia and enhanced sensitivity to light, sound, and odors. Our objective was to identify physiological changes in cortical regions in migraine patients using painful heat and functional magnetic resonance imaging (fMRI) and the structural basis for such changes using diffusion tensor imaging (DTI). In 11 interictal patients, painful heat threshold + 1°C was applied unilaterally to the forehead during fMRI scanning. Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
234
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(257 citation statements)
references
References 99 publications
19
234
3
1
Order By: Relevance
“…The reduced cardiac vagal modulation in the newly diagnosed migraine patients of the present series is shared by several groups of researchers [16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 52%
“…The reduced cardiac vagal modulation in the newly diagnosed migraine patients of the present series is shared by several groups of researchers [16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 52%
“…Moulton and colleagues [27] have measured brainstem fMRI responses to noxious heat in migraine subjects, showing a reduced activity at the level of the nucleus cuneiformis, a component of brainstem pain modulatory circuits. After this work, similar experiments have been performed in migraine subjects and the same research group has shown an increased BOLD response of the anterior temporal pole in migraine subjects during the interictal period [28]. Similarly, during a moderate noxious stimulus we have demonstrated a significantly greater activation in the anterior cingulate cortex (ACC) and a significantly lower activation in the bilateral somatosensory cortex (SCC) during a severe noxious stimulus, in MwoA patients during interictal period compared to healthy controls (HC) [29].…”
Section: Discussionmentioning
confidence: 80%
“…52 2. Alterations in descending pain modulation are also inferred from brain imaging, 53,54 suggesting that in migraine, like in many chronic pain diseases, ascending nociception is facilitated by diminished inhibitory (or increased facilitory) systems. It is thought that these begin to functionally fail as migraine undergoes chronification.…”
mentioning
confidence: 99%